Analysis of the Use of Kemangi Leaves in Reducing Albus Fluor in Acceptor Women KB IUD in Malang Archipelago Hospital - Indarti, Daru; Indasah; Nurdina (Master of Public Health Program Universitas STRADA Indonesia, 2020)
Flour Albus is a symptom that is very often experienced by most women. This disorder is the second problem after menstrual disorders. Flour Albus is often not taken seriously by women. In fact, vaginal discharge can be an indication of an illness. Almost all women have experienced vaginal discharge. Therefore the researcher was interested in examining the analysis of the use of basil leaves in reducing flour albus in women using KB IUD acceptors in the Indonesian Army Hospital. The purpose of the study was to analyze the effect of using basil leaves in reducing flour albus in women using KB IUD acceptors in the Indonesian Army Hospital Malang. The research design used is quantitative research with a True Experimental Design approach. Instrument data used questionnaire sheets using the Paired T-test and Anova test. The results of the Paired T-test analysis said that p value = 0,000 for the use of 2 grams of kenagi leaves and p value = 0,006 for the use of 1 gram of basil leaves so that H0 was rejected which meant that there was an effect of 2 gram and 1 gram of Basil Leaf Use In Women with KB IUD Acceptor Users At Malang Army Hospital. From the results of the Anova test, it is known that the value of p value is 0.191> α (0.05), it can be concluded that the administration of basil leaves 2 grams and 1 gram is the same and the difference in mean giving between the two is not significant. It is expected that respondents can make the habit of consuming basil leaves as a prevention and treatment for vaginal discharge experienced when using IUD KB acceptors. And for the next researcher, they can make basil leaves in capsule form to make them easier to consume